Active surface deformations detected by precise levelling surveys in the Afyon-Aksehir Graben, Western Anatolia, Turkey - Triyakioglu, Ibrahim; Yigit, Cemal Ozer; Ozkaymak, Caglar; Baybura, Tamer; Yilmaz, Mustafa; Ugur, Mehmet Ali; Yalcin, Mustafa; Poyraz, Fatih; Sozbilir, Hasan; Gulal, Vahap Engin (UNIV ZAGREB , ANDRIJA MOHOROVICIC GEOPHYS INST, 2019)
In the actively deforming region of western Anatolia, crustal deformation is accommodated by destructive earthquakes and a variety of aseismic events. In this study, we investigated the 2016-2017 aseismic sequence located in the Bolvadin Fault, one of the segments of the Aksehir-Simav Fault System of western Anatolia by analysing surface deformation derived from detailed geological mapping. Our findings suggest that surface deformation in the Bolvadin Fault is accommodated by aseismic episodes. During the field studies in the Bolvadin area, progressive surface deformations, such as surface faults and earth fissures with a length of 800 meters to 3 kilometres and strike of N15 degrees E to N70 degrees E were mapped on a 1/5000 scale. Furthermore. a levelling network was established to calculate the vertical displacements and deformation rate along the surface deformations. Precision level measurements were undertaken in 2016 and 2017. On the routes to the NW of the Bolvadin settlement, a vertical deformation rate of 30 mm/yr was detected in the period of 2016-2017, and a large deformation rate of 40 mm/yr was detected in the same period.
Keywords: Aksehir-Simav fault system; surface deformation; digital levelling; Bolvadin fault; Western Anatolia; LAND SUBSIDENCE; VALLEY; FAULT; GPS; Geochemistry & Geophysics; Geology; Meteorology & Atmospheric Sciences